Nasopharyngeal carcinoma in children and adolescents: The EXPeRT/PARTNER diagnostic and therapeutic recommendations. (12th April 2021) - Ben‐Ami, Tal; Kontny, Udo; Surun, Aurore; Brecht, Ines B.; Almaraz, Ricardo López; Dragomir, Monica; Pourtsidis, Apostolos; Casanova, Michela; Fresneau, Brice; Bisogno, Gianni; Schneider, Dominik T.; Reguerre, Yves; et al.
Abstract: Nasopharyngeal carcinoma (NPC) is a rare pediatric tumor. Collaborative studies performed over the last decades showed improved results compared to historical data, but standardized guidelines for diagnosis and management of pediatric NPC are still unavailable. This study presents a European consensus guideline for the diagnosis and treatment of pediatric NPC developed by the European Cooperative Study Group for Pediatric Rare Tumors (EXPeRT). Main recommendations include induction chemotherapy with cisplatin and 5‐flurouracil, concomitant chemoradiotherapy in advanced disease, and to consider maintenance treatment with interferon beta (IFN‐β) for selected high‐risk patients. Dose adjustments of radiotherapy based on response to induction chemotherapy may decrease the rates of long‐term treatment‐related complications that affect most of the survivors.